The effect of influencer’s credibility and product prices on the purchase intention of Maybelline products in the Tiktok Shop application - Thamira Umardi; Hamsani Hamsani; Reniati Reniati (Institute of Computer Science (IOCS), 2023)
The Covid-19 pandemic has forced everyone to stay and spend more time at home. It had makes the trend for beauty and health care became increased, so the product transactions were also high. This condition supported by the presence of influencers who often to review the beauty products in the Tiktok application, one of them was Tasya Farasya. This study aims to determined and analyzed whether the influencer’s credibility and product prices variables had an effect on the purchase intention of Maybelline products in the Tiktok Shop application. This research used a quantitative approach with the sample of 100 respondent with the criteria being women users of the Tiktok social media who have seen or accessed Tasya Farasya Tiktok account and are currently using Maybelline brand cosmetics. Purposive sampling was used to gather samples using a non-probability sampling strategy. The method for analyzing the data used multiple linear regressions with IBM Statistics 24. The result of data analysis revealed that, partially each of independent variables, which is influencer’s credibility and product prices, had a positive and significant effect on the purchase intention of Maybelline products in the Tiktok Shop application. And simultaneously the two of independent variables also had a positive and significant effect on the purchase intention of Maybelline products in the Tiktok Shop application, so it can be inferred that all of the hypotheses were accepted.